The relationship between otitis media and literacy outcomes of urban indigenous Australian school children - Timms, Lydia Jane (Curtin University, 2015)
The literacy skills of 57 Indigenous Australian early-school students in Perth were compared by their ear health status where hearing loss (HL) and otitis media (OM) (highly prevalent in the population) was tested up to five times in the year prior to the culturally modified literacy assessment. No significant differences were found. The students showed overall improvement on all outcomes following a 15 hour targeted phonological awareness intervention. No differences in improvement were shown between the children with and without OM/HL.